Design and assessment of a stainless-steel multi-step cascade solar photocatalytic reactor for simultaneous decontamination and disinfection of water - Isabel Espinoza-Pavón; Ilaria Berruti; Cristina Monteserín; Miren Blanco; Sergi Navarro; Isabel Oller; Sixto Malato; Samira Nahim-Granados; María Inmaculada Polo-López (Chemical Engineering Journal, 2026)

Improving ozone-based processes for the degradation of paraquat and diquat as persistent pesticides - Joseph Soto-Verjel; Paula Serrano-Tarí; Salvador Villamizar; Ana Ruiz-Delgado; Aymer Maturana-Córdoba; Isabel Oller (Environmental Science and Pollution Research, 2026)

Assessment of a novel sequential treatment train based on natural and low-cost technologies for wastewater reclamation at demonstrative scale: A multiparametric analysis of EU regulated indicators - Alba Hernández-Zanoletty; Ilaria Berruti; Eva Jambrina-Hernández; Isabel Oller; M. Inmaculada Polo-López; Pedro Simón; Patricia Plaza-Bolaños; Ana Agüera (Science of The Total Environment, 2025)

Effect of microplastics on tertiary/quaternary treatment of urban wastewater: Fe-biochar/peroxymonosulfate/sunlight vs solar photo-Fenton - Mister Adeel; Carla Fernanda Grasel Frois; Ilaria Berruti; Carla Sirtori; Isabel Oller; Sixto Malato; Luigi Rizzo (Journal of Environmental Management, 2025)

Up-scaling solar photochemistry quaternary treatment of urban wastewaters to a demonstrative level - Alba Hernández-Zanoletty; Ilaria Berruti; Eva Jambrina-Hernández; Isabel Oller; M. Inmaculada Polo-López; Patricia Plaza-Bolaños; Ana Agüera (Journal of Environmental Chemical Engineering, 2025)

Upgrade constructed wetlands wastewater quality by solar-driven photochemical quaternary treatments in raceway pond reactor at pilot plant scale - Alba Hernández-Zanoletty; Isabel Oller; M. Inmaculada Polo-López; Eva Jambrina-Hernández; Patricia Plaza-Bolaños; Ana Agüera (Science of The Total Environment, 2025)

Toward the development of an ML-driven decision support system for wastewater treatment: A bacterial inactivation prediction approach in solar photochemical processes - Pavel Pascacio; David J. Vicente; Ilaria Berruti; Samira Nahim Granados; Isabel Oller; M. Inmaculada Polo-López; Fernando Salazar (Journal of Environmental Management, 2025)

Improving water security and sanitation in rural areas: comparative evaluation of TiO2 and photo-Fenton processes for rural wastewater treatment and reuse - Yasmin Cherni; Djebali Kais; Hamadi Kallali; Mohamed Ali Wahab; Samira Melki; Jihene Tayahi; Isabel Oller; Plakas Konstantinos (Euro-Mediterranean Journal for Environmental Integration, 2024)

Assessment of antibiotic-resistant infection risks associated with reclaimed wastewater irrigation in intensive tomato cultivation - Samira Nahim-Granados; Hunter Quon; María Inmaculada Polo-López; Isabel Oller; Ana Agüera; Sunny Jiang (Water Research, 2024)

Assessment of new immobilized photocatalysts based on TiO2 for wastewater decontamination - Alba Hernández-Zanoletty; Oscar Cabezuelo; Agustín París-Reche; Isabel Oller; M. Inmaculada Polo-López; Ana Agüera; Patricia Plaza; M. Luisa Marín; Francisco Boscá; Sixto Malato (Journal of Environmental Chemical Engineering, 2023)

Assessment of solar water disinfection enhancement with H2O2 and dissolved oxygen on inactivating different waterborne pathogens - Azahara Martínez-García; Samira Nahim-Granados; Ilaria Berruti; Isabel Oller; María Inmaculada Polo-López (Journal of Environmental Chemical Engineering, 2023)

Solar photo-Fenton optimization at neutral pH for microcontaminant removal at pilot plant scale - Mercedes Hinojosa; Isabel Oller; José María Quiroga; Sixto Malato; Agata Egea-Corbacho; Asunción Acevedo-Merino (Environmental Science and Pollution Research, 2023)
The increasing occurrence of micropollutants in natural water bodies has medium to long-term effects on both aquatic life and human health. The aim of this study is to optimize the degradation of two pharmaceutical pollutants of emerging concern: amoxicillin and acetaminophen in aqueous solution at laboratory and pilot scale, by solar photo-Fenton process carried out at neutral pH using ethylenediamine-N,N′-disuccinic acid (EDDS) as a complexing agent to maintain iron in solution. The initial concentration of each compound was set at 1 mg/L dissolved in a simulated effluent from a municipal wastewater treatment plant (MWTP). A factorial experimental design and its surface response analysis were used to optimize the operating parameters to achieve the highest initial degradation rate of each target. The evolution of the degradation process was measured by ultra-performance liquid chromatography (UPLC/UV), obtaining elimination rates above 90% for both contaminants. Statistical study showed the optimum concentrations of Fe(III) at 3 mg/L at an Fe-EDDS ratio of 1:2 and 2.75 mg/L H 2 O 2 for the almost complete removal of the target compounds by solar photo-Fenton process. Validation of the experimental design was successfully carried out with actual MWTP effluent spiked with 100 μg/L of amoxicillin and acetaminophen, each at pilot plant scale.

Elimination of sulfamethoxazole by anodic oxidation using mixed metal oxide anodes - Yeney Lauzurique; Sara Miralles-Cuevas; Mariel Godoy; Pamela Sepúlveda; Soledad Bollo; Alejandro Cabrera-Reina; César Huiliñir; Sixto Malato; Isabel Oller; Ricardo Salazar-González (Journal of Water Process Engineering, 2023)

Ozonation Vs sequential solar driven processes as simultaneous tertiary and quaternary treatments of urban wastewater: A life cycle assessment comparison - Gulnara Maniakova; María Inmaculada Polo López; Isabel Oller; Sixto Malato; Luigi Rizzo (Journal of Cleaner Production, 2023)

Peroxymonosulfate/Solar process for urban wastewater purification at a pilot plant scale: A techno-economic assessment - Ilaria Berruti; Samira Nahim-Granados; María Jesús Abeledo-Lameiro; Isabel Oller; María Inmaculada Polo-López (Science of The Total Environment, 2023)

Efficient solar disinfection (SODIS) using polypropylene based transparent jerrycans: An investigation into its effectiveness, viability, and water sample toxicity - Kris O’Dowd; Azahara Martínez-García; Isabel Oller; María Inmaculada Polo-López; Seila Couso-Pérez; Elvira Ares-Mazás; Hipólito Gómez-Couso; Ángela García-Gil; Javier Marugán; Ramesh Marasini; Kevin G. McGuigan; Suresh C. Pillai (Journal of Environmental Chemical Engineering, 2023)

Individual and combined effect of ions species and organic matter on the removal of microcontaminants by Fe3+-EDDS/solar-light activated persulfate - Alejandro Cabrera-Reina; Marina Aliste; María Inmaculada Polo-López; Sixto Malato; Isabel Oller (Water Research, 2023)

Olive mill wastewater reuse to enable solar photo-Fenton-like processes for the elimination of priority substances in municipal wastewater treatment plant effluents - Ana Ruíz-Delgado; Melina Antonella Roccamante; Sixto Malato; Ana Agüera; Isabel Oller (Environmental Science and Pollution Research, 2020)

Reliable analysis of chlorophenoxy herbicides in soil and water by magnetic solid phase extraction and liquid chromatography - Ainhoa Oller-Ruiz; Isabel Garrido; Pilar Viñas; Natalia Campillo; José Fenoll; Manuel Hernández-Córdoba (Environmental Chemistry Letters, 2018)